Changes in cross-sectional measurements of masseter, medial pterygoid muscles, ramus, condyle and occlusal force after bi-maxillary surgery. Issue 3 (March 2019) - Takayama, Akihiro; Ueki, Koichiro; Moroi, Akinori; Tsutsui, Takamitsu; Saito, Yuki; Sato, Momoko; Yoshizawa, Kunio
Abstract: Purpose: The purpose of this study was to examine changes in masseter and medial pterygoid muscles, ramus, condyle and occlusal force after bi-maxillary surgery in class II and III patients. Subjects and methods: The subjects were 42 patients (84 sides) who underwent sagittal split ramus osteotomy with Le Fort I osteotomy (21 class II cases: mandibular advancement and 21 class III cases: mandibular setback). The cross-sectional measurements of the masseter and medial pterygoid muscles, ramus and condyle were measured in horizontal plane images by computed tomography (CT), before and 1 year after the operation. Occlusal force and contact area were also recorded before and 1 year after the operation. Results: Preoperatively, class II was significantly larger than class III in masseter width (P = 0.0068), masseter area (P < 0.0001) and medial pterygoid length (P < 0.0001). However, class II was significantly smaller than class III in medial pterygoid width (P < 0.0001). After 1 year, class II was significantly smaller than class III in masseter length (P = 0.0017). Class II was still larger than class III in medial pterygoid area after 1 year (P = 0.0343). Class II was significantly larger than class III in condylar angle pre-operatively (P < 0.0001) and after 1 year (P = 0.0006). After 1 year, class II decreased significantly more than class III in condylar thickness (P = 0.0020), condylar width (P < 0.0001) and condylar area (P < 0.0001). Conclusion: This study suggested that changes in the cross-sectional measurements of masseter and medial pterygoid muscles and the condyle differed between class II and class III patients, although occlusal force did not significantly change 1 year after surgery in both groups.